The New Mission for Multinationals - Santos, José; Williamson, Peter; Srikanth, Kannan; Ghemawat, Pankaj; Rangan, U.; Luo, Yadong; Yip, George; Doh, Jonathan (MIT Sloan Management Review, 2015)
Not long ago, many observers worried that ever-expanding multinationals - many of which had revenues exceeding the gross domestic products of smaller countries - were going to take over the world. But as globalization marches onward, powerful local companies are increasingly winning out against multinational competitors. This is especially true in emerging markets, where multinationals are assumed to enjoy superiority and CEOs are counting on growth. In China, the ice cream, laundry detergent and appliance markets provide interesting examples of this phenomenon. Despite the presence of multinationals in these markets, the market-share leaders are local companies. A similar pattern is being repeated in other emerging markets. The authors note, however, that in some cases multinationals have been able to resist the market gains of local competition, whether through first-mover advantages or by acquiring the leading local players and nurturing their local identity and strengths. For decades, multinationals were able to make good returns by acting as efficient global conduits for assets that were difficult to transfer, including intangibles such as product designs, technologies, management systems and company cultures. Transfers within the multinational company were more efficient than obtaining those assets through open-market transactions. However, a number of forces have been eroding that advantage. First, in the drive to reduce costs, established multinationals increasingly focused on activities with the highest returns. This meant that lower-value activities were outsourced and often offshored to emerging economies, creating global markets in which local companies can also source components and services. The result is that once-closed value chains have been opened up, enabling local players to source "plug-and-play" modules that can be combined to create products very similar - and sometimes superior - to those of foreign multinationals. If multinationals are to succeed against local competition in emerging markets, the authors write, they need to move beyond the credo of "integrate globally and adapt locally." They will need to create new advantages in target markets by integrating their businesses with the local commercial networks and the soci ...